The Role of p21-Activated Kinases in Cancer and Beyond: Where Are We Heading? - Liu, Hui; Liu, Kangdong; Dong, Zigang (Frontiers in Cell and Developmental Biology, 2021)
The p21-activated kinases (PAKs), downstream effectors of Ras related Rho GTPase Cdc42 and Rac, are serine/threonine kinases. Biologically, PAKs participate in various cellular processes, including growth, apoptosis, mitosis, immune response, motility, inflammation, and gene expression, making PAKs as the nexus of several pathogenic and oncogenic signaling pathways. PAKs were proved to play critical roles in human diseases, including cancer, infectious diseases, neurological disorders, diabetes, pancreatic acinar diseases, and cardiac disorders. In this review, we systematically discuss the structure, function, alteration, and molecular mechanisms of PAKs that involved in the pathogenic and oncogenic effects, as well as PAKs inhibitors which may be developed and deployed in cancer therapy， anti-viral infection, and other diseases. Furthermore, we highlight the critical questions of PAKs in future research, which provide an opportunity to offer input and guidance on new directions for PAKs in pathogenic, oncogenic, and drug discovery research.